Answer:
(0,6)
Step-by-step explanation:
The given system of equations is
![y = \frac{3}{2}x + 6](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B3%7D%7B2%7Dx%20%2B%206)
and
![\frac{1}{2}y - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7Dy%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203)
We substitute the first equation into the second equation to get:
![\frac{1}{2} ( \frac{3}{2}x + 6) - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20%28%20%5Cfrac%7B3%7D%7B2%7Dx%20%2B%206%29%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203)
We expand to get:
![\frac{3}{4} x + 3 - \frac{1}{4}x = 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20x%20%2B%203%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203%20)
We group similar terms to get:
![\frac{3}{4}x - \frac{1}{4}x = 3 - 3](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7Dx%20-%20%20%5Cfrac%7B1%7D%7B4%7Dx%20%3D%203%20-%203)
![\frac{1}{2}x = 0](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7Dx%20%3D%200)
![x = 0](https://tex.z-dn.net/?f=x%20%3D%200)
Put x=0 in to the first equation to get:
![y = 6](https://tex.z-dn.net/?f=y%20%3D%206)
Therefore the solution is (0,6)
Answer: 4:00 pm
Step-by-step explanation:
Answer:
a = 150
Step-by-step explanation:
The sum of the internal angles of an octagon is 1080°.
(There are four
and 4
, they sum to 1080°)
![4a + 480 = 1080](https://tex.z-dn.net/?f=4a%20%2B%20480%20%3D%201080)
![4a = 600](https://tex.z-dn.net/?f=4a%20%3D%20600)
![a = 150](https://tex.z-dn.net/?f=a%20%3D%20150)
Hope this helps :)
Answer:
510m
Step-by-step explanation:
that should be it it's been a while since I did area